Action research: A mechanism for active engagement of clinical nurses in a program of research. (27th February 2020) - Alomari, Albara; Wilson, Val; Lewis, Joanne
Abstract: This study aimed to explore the outcomes of active participation in an action research project on building the research capacity of clinical nurses. In this qualitative research study, six registered nurses volunteered to participate in the action research team. None of the nurses reported having any prior research experience. This study was part of a larger three‐phase project. The nurses were required to reflect on the data about their medication practice of phase 1, develop and implement a bundle of interventions in phase 2 to improve medication safety, and evaluate the effectiveness of these interventions in phase 3. We report the nurses' participation in Action Research during phase 2. Meeting minutes and six semistructured interviews were thematically analyzed. The results showed that after receiving support to enhance their research skills from the research team, the nurses were empowered to perform and lead clinical nursing research project. Nurses were able to take ownership of the research process and outcomes and were then able to translate their new research knowledge and skills into their clinical practice by building their own research capacity.